ANALISIS KELAYAKAN INVESTASI DALAM PENGAJUAN FASILITAS KREDIT PADA PT. XYZ - Puspa Akbar Darmawan; Suparno Suparno (Ekonis: Jurnal Ekonomi dan Bisnis, 2022)
Abstract: PT. XYZ working in fertilizer trade to fulfill XYZ Group's fertilizer needs. The fertilizer supply is constrained by PT XYZ’s suppliers. In order to meet these fertilizer needs, PT. XYZ plans to build NPK plant located in Central Java. Investation is planned to use a bank credit facility. Based on the requirement in the credit application, an analysis of investment feasibility is carried out on the submission of PT. XYZ credit facilities. This research was conducted using a qualitative approach and a quantitative approach. A qualitative approach is used to examine non-financial aspects including review of the NPK fertilizer industry and business plan analysis. The quantitative approach is used to examine financial aspects including financial projections and sensitivity analysis.  Review from NPK fertilizer industry, Indonesia have a market prospect of 4.8 million tons NPK fertilizer needs for palm oil plantation sector. The business plan for the construction of the NPK fertilizer plant includes a 300,000 MTPY capacity, chemical granulation based technology, fertilizer product with formulas 12-12-17 and 13-6-27, and Engineering, Procurement and Construction duration of project is 26 months.  The results showed that the construction of NPK Fertilizer Plant was feasible in business and feasible to be financed with credit from creditors with an investment credit of Rp. 541,725,406,300 and working capital loans of Rp. 92,245,261,932, -. The feasibility of providing credit facilities is seen from the positive cash flow ability of NPK fertilizer sales and financial indicators, namely the Payback Period for 5.62 years, NPV (DF 11%) of Rp. 756,104,248,537, -, Internal Rate of Return 23.25%, Profitability Index 1.88.Keywords: NPK Fertilizer Industry, Business Plan Analysis, Financial Projection, Sensitivity Analysis, Payback Period, Internal Rate of Return, Net Present Value, Profitability Index